The Integration of Psychological Aspects and Islamic Values in Domestic Dispute Mediation in Religious Courts - Sofia Gussevi; Encup Supriatna; Irfan Fahmi; Ujang Abidin; Maida Zahra (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
Mediation is a form of Alternative Dispute Resolution that aims to achieve amicable settlements between disputing parties. In the context of family disputes in Indonesia, mediation plays a strategic role in preventing divorce and maintaining family unity and harmony. However, the effectiveness of mediation is influenced not only by legal and procedural factors but also by the psychological conditions and dynamics of the parties involved. This study examines the role of psychological aspects in determining the success of family dispute mediation in the Religious Courts of Indonesia. Using an empirical legal research design with a qualitative sociological approach, primary data were collected through in-depth interviews with judges, mediators, and disputing parties at the Religious Court of Purwakarta, supported by direct observation of mediation sessions. The findings reveal that mediators who understand the psychological dynamics of the parties are more capable of creating a conducive mediation environment, managing emotions effectively, and facilitating constructive communication. Psychological aspects significantly contribute to the achievement of amicable agreements and to the sustainability of post-mediation relationships. Accordingly, the integration of psychological approaches into the training and practice of family mediation in the Religious Courts should be strengthened to enhance the effectiveness of family dispute resolution in a peaceful, humane, and just manner. This study aligns with the principles of Islamic law, particularly the concepts of islah (reconciliation) and shulh (amicable settlement), as well as the objectives of maqāṣid al-sharīʿah, especially hifz al-nasl (the protection of progeny and family integrity).